Molluscicidal activities of medicinal plants from eastern China against Oncomelania hupensis, the intermediate host of Schistosoma japonicum - Han,Bang-xing (2010)
In a search for natural products that could be used to control schistosomiasis, nineteen extracts of eleven medicinal plants from eastern China have been tested for molluscicidal activity against snail Oncomelania hupensis. The n-butanol fraction of the fresh leaf from Buddleja lindleyana Fortune, Buddlejaceae, showed significant activity against the snails. Statistical analysis revealed that the LC50 and LC90 values for the n-butanol fraction were 39.91 mg L-1 and 59.28 mg L-1 for 48 h, respectively. Otherwise, the LC50 values for the n-butanol fraction to zebrafish was 403.24 mg L-1 for 48 h. Therefore, the n-butanol fraction of the fresh leaf from B. lindleyana may be a potent and safe molluscicides.